2023
DOI: 10.1007/s10856-023-06742-2
|View full text |Cite
|
Sign up to set email alerts
|

Host–device interactions: exposure of lung epithelial cells and fibroblasts to nickel, titanium, or nitinol affect proliferation, reactive oxygen species production, and cellular signaling

Abstract: Endoscopic implantation of medical devices for the treatment of lung diseases, including airway stents, unidirectional valves and coils, is readily used to treat central airway disease and emphysema. However, granulation and fibrotic tissue formation impairs treatment effectiveness. To date little is known about the interaction between implanted devices, often made from metals, such as nickel, titanium or nitinol, and cells in the airways. Here, we study the response of lung epithelial cells and fibroblasts to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The results of our study are in agreement with recently reported evidence that human lung fibroblasts displayed altered cell signaling when indirectly exposed to nitinol alloys [39]. The Ni 2+ ions released from the alloy increased free radical production in cells, suggesting metal toxicity.…”
Section: Discussionsupporting
confidence: 93%
“…The results of our study are in agreement with recently reported evidence that human lung fibroblasts displayed altered cell signaling when indirectly exposed to nitinol alloys [39]. The Ni 2+ ions released from the alloy increased free radical production in cells, suggesting metal toxicity.…”
Section: Discussionsupporting
confidence: 93%
“…In biomaterial studies, T1 relaxometry has also been used to reveal whether free radicals are generated in lung epithelial cells exposed to nickel, titanium, and nitinol. 15 It is worth mentioning that T1 relaxometry has already shown great potential in monitoring the free radical generation during e.g. , chemical reactions, 16 shear stress in endothelial cells, 17 response of bacteria to antibiotics, 18 or upon viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…, chemical reactions, 16 shear stress in endothelial cells, 17 response of bacteria to antibiotics, 18 or upon viral infections. 19 The versatility of the technique has been demonstrated while detecting free radicals in various cell cultures, including the already-mentioned epithelial 15 and endothelial 17 cells, as well as dendritic cells, 20 HeLa cells, 21 macrophages, 22 granulosa cells, 23 or sperm cells. 24 The method enables measurements in single-cell organelles, such as mitochondria, 25 or particular cellular locations, such as acrosomes.…”
Section: Introductionmentioning
confidence: 99%